URGENSI KOMPETENSI KEPEMIMPINAN BAGI KEPALA SEKOLAH DAN MADRASAH - Muhidin Arifin; Taufikurrahman; Mulyono; Amruddin; Iman Saifullah (al-Afkar, Journal For Islamic Studies, 2022)
THE URGENCE OF LEADERSHIP COMPETENCY FOR PRINCIPLES AND MADRASAH This research is aimed at describing what, why, and how or what strengths or potentials should be possessed by the leadership of principals and madrassas. The leadership role of the head of the madrassa will affect the back and forth of a madrassa. Principals and madrassas as leaders must be able to motivate and contribute, direct and educate their subordinates, because the success of a leader in managing his institution in achieving goals, depends heavily on the potential he has, therefore it will arise how or what kind of potential should be owned by a principal and madrasah for the progress of his school. This article is written using qualitative methods of descriptive or with references from journal articles. From this research, it was produced that the potential that must be possessed by the principal and madrasah, namely: personality competencies( principals and madrassas must be noble, authoritative and become for learners), managerial competence (the principal must be integrity, cooperation, communication, orientation on results, public service, self-development, managing change). Corporate competence (technical skills, making and decision-making, organizing ability). Supervisory competence (planning a supervise program, academic in order to increase teacher professionalism). Social competence (getting along effectively with learners and the social environment of the surrounding community).